Classification of Parabacteroides distasonis and other Bacteroidetes using O- antigen virulence gene: RfbA-Typing and hypothesis for pathogenic vs. probiotic strain differentiation. (31st December 2022) - Bank, Nicholas C.; Singh, Vaidhvi; Rodriguez-Palacios, Alex
ABSTRACT: Parabacteroides distasonis ( Pdis ) is the type species for the new Parabacteroides genus, and a gut commensal of the Bacteroidetes phylum. Emerging reports (primarily based on reference strain/ATCC-8503) concerningly propose that long-known opportunistic pathogen Pdis is a probiotic. We posit there is an urgent need to characterize the pathogenicity of Pdis strain-strain variability. Unfortunately, no methods/insights exist to classify Bacteroidetes for this purpose. Herein, we developed a virulence gene-based classification system for Pdis and Bacteroidetes to facilitate pathogenic-vs-probiotic characterization. We used DNA in silico methods to develop a system based on the virulence (lipopolysaccharide/bacterial wall) ' rfbA O-antigen-synthesis gene'. We then performed phylogenetic analysis of rfbA from fourteen Pdis complete genomes (21 genes), other Parabacteroides, Bacteroidetes, and Enterobacteriaceae ; and proposed a PCR-based Restriction-Fragment Length Polymorphism method. Cluster analysis revealed that Pdis can be classified into four lineages (based on gene gaps/insertions) which we designated rfbA -Types I, II, III, and IV. In context, we found 14 additional rfbA -types (I–XVIII) interspersed with numerous Bacteroidetes and pathogenic Enterobacteriaceae forming three major " rfbA -superclusters." For laboratory rfbA -Typing implementation, we developed a PCR-primer strategy to amplify Pdis rfbA genes (100%-specificity) to conduct MboII-RFLP and sub-classify Pdis. In-silico primers for other Bacteroidetes are proposed/discussed. Comparative analysis of lipopolysaccharide/lipid-A gene lpxK confirmed rfbA as highly discriminant. In conclusion, rfbA -Typing classifies Bacteroidetes/Pdis into unique clusters/superclusters given rfbA copy/sequence variability. Analysis revealed that most pathogenic  Pdis  strains are single-copy  rfbA -Type I . The relevance of the rfbA strain variability in disease might depend on their hypothetical modulatory interactions with other O-antigens/lipopolysaccharides and TLR4 lipopolysaccharide-receptors in human/animal cells.